2015
DOI: 10.1016/j.nanoen.2014.12.024
|View full text |Cite
|
Sign up to set email alerts
|

Soluble polysulphide sorption using carbon nanotube forest for enhancing cycle performance in a lithium–sulphur battery

Abstract: The rapid capacity decay of lithium-sulphur batteries has been a significant obstacle for practical application, which is generally considered to arise from dissolution of lithium polysulphide in the electrolyte and diffusion away from the cathode. As the lithium content in the polysuphide inceases with further discharge, capacity decay occurs also from the passivating effects by the formation of insoluble sulphides, further amplified by volume increase. More recently, weakening of sulphur adhesion to carbon w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(40 citation statements)
references
References 48 publications
1
39
0
Order By: Relevance
“…The LiPS‐trapping mechanism is explained considering the complex disordered, 3D pore network of the mesoC coating, which forms a highly intricate pathway against the migration of large LiPSs to the anode side. In addition, Xi et al recently demonstrated that LiPS species are interfacially adsorbed onto the carbon wall of CNTs . Such physical adsorption can also take place on the extensive interface of the large pore volume, mesoC coating, favoring the retention of the active sulfur material on the cathode side.…”
Section: Resultsmentioning
confidence: 99%
“…The LiPS‐trapping mechanism is explained considering the complex disordered, 3D pore network of the mesoC coating, which forms a highly intricate pathway against the migration of large LiPSs to the anode side. In addition, Xi et al recently demonstrated that LiPS species are interfacially adsorbed onto the carbon wall of CNTs . Such physical adsorption can also take place on the extensive interface of the large pore volume, mesoC coating, favoring the retention of the active sulfur material on the cathode side.…”
Section: Resultsmentioning
confidence: 99%
“…The use of highly conductive carbon is an effective route to accommodate sulfur as a composite cathode for lithium ion storage . A PGF with large surface area and hierarchically porous structure is expected to be a promising conductive scaffold to accommodate sulfur for Li‐S batteries.…”
Section: Resultsmentioning
confidence: 99%
“…The superior lithium ion storage performance of the PGF‐based sulfur electrode was attributed to the following aspects: (1) The mesoporous PGF with highly conductive graphene building blocks rendering intimate contact to sulfur species, which guaranteed high sulfur utilization of 71% (corresponding to 1187 mAh g −1 ) at a high current density of 1.0 C; (2) the large hollow cavity of PGFs with significant contribution of large mesopores accommodating the volume expansion of sulfur, leading to superior cycling stability of ≈80% over 500 cycles; (3) robust electron pathways in graphene walls of the PGFs, as well as 3D interconnected macro/mesopores as ion channels for rapid transportation of lithium ions, resulting in 48.4% retention when the current density increased from 0.1 to 5.0 C; and (4) highly chemically and mechanically robust PGF carbon skeletons for long‐term durability. Compared with DTG, CVD graphene, reduced graphene oxide, cetyltrimethyl ammonium bromide‐modified sulfur‐graphene oxide, nitrogen‐doped graphene, porous carbon, CNTs, or their hybrids, the PGF reported herein is a novel nano­reactor for electrochemical reactions requiring large volume change toleration, high surface area, interconnected electron highways and ion diffusion channels, and that benefit from the introduction of an abundance of large mesopores (3–25 nm) into 3D graphene frameworks. The combination of Kirkendall diffusion and the evaporation of volatile metal is an effective route to fabricate hierarchical oxide templates for CVD assembly of PGFs with anticipated large mesopores.…”
Section: Resultsmentioning
confidence: 99%
“…The lithium-sulfur (Li-S) batteries have become one of the most attractive candidates that could surpass current lithium-ion batteries (LIBs) to achieve high charge capacity of 1675 mAh/g and energy density of 2500 Wh/kg and meet the demands of emerging electric vehicles 1,2 . High natural abundance, low cost, and environmental-friendliness of sulfur bestows sulfur a promising raw material of cathode for Li-S rechargeable batteries 1,3,4 .…”
Section: Introductionmentioning
confidence: 99%